Business intelligence in higher education : managing the relationships with students - Piedade, Maria Beatriz (2009)
The closely monitoring of the students’ academic activities, the evaluation of their academic success and the approximation to their day-by-day academic activities are key factors in the promotion of the student’s academic success in higher education institutions. To be possible the implementation of monitoring processes and activities, it is essential the acquisition of knowledge about the students and their academic behaviour. This knowledge supports the decision-making associated with teaching-learning process, enhancing an effective institution-student relationship. This paper presents a Student Relationship Management (SRM) system that is under development. The SRM system supports the SRM concept and practice and has been implemented using concepts and technologies associated to the Business Intelligence systems. To demonstrate the SRM system relevance in the process of acquisition of knowledge about the students and in the support of actions and decisions based on such knowledge, an application case carried out in a real context is also presented.